Design and evaluation of a multifunctional plate sediment trap suitable for subaqueous and floodplain environments. Issue 2 (13th June 2014) - Schoelynck, Jonas; Oosterlee, Lotte; De Groote, Toon; Maris, Tom; Struyf, Eric; Meire, Patrick; Temmerman, Stijn
Abstract In recent years, it has become increasingly clear that two‐way interactions between organisms and landscape‐forming processes play a key role in the evolution of many aquatic ecosystems. To be able to compare sedimentation processes among different environments, a standardized method that is generally applicable is necessary. Current methods are usually designed for one environment only or are unreliable in the presence of vegetation. This paper presents the functionality of a plate sediment trap with a lid in combination with a filter paper, which enables the measurement of sedimentation rates in both permanently subaqueous environments and periodically flooded wetlands. We first present the trap design and demonstrate its functionality. No significant differences were found between replicates, nor was there any indication of a trap size effect on the sedimentation rate. Secondly, we demonstrate its applicability in periodically flooded and permanently subaqueous environments and in the presence or absence of vegetation. It is concluded that the use of a standardized method and equipment makes it possible to compare (bio)geomorphological changes in totally different environments. Copyright © 2014 John Wiley & Sons, Ltd.